Impacts of seasonal climate communication strategies on farm management and livelihoods in Wote, Kenya - Rao, K.P.C.; Hansen, James; Njiru E; Githungo WN; Oyoo A (2015)
This study was undertaken in Wote division, Makueni district, Eastern province, Kenya, to test the effectiveness of different methods of communicating downscaled seasonal climate forecast information, and to assess its impact on management and productivity of smallholder farms. The communication methods tested include training workshops aimed at helping farmers understand downscaled probabilistic climate forecast information, agro-advisories that combined forecast information with advice on potential management options, and a combination of training and agro-advisory workshops. The study was conducted with about 120 farmers, 10 from each of 12 villages selected randomly from the villages that are within a 5 km radius from Kampi Ya Mawe research station for which long-term climate records are available, during the 2011-2012 short rain season. Three surveys, implemented during the pre-, mid- and end-season periods, captured changes in management, productivity, and attitudes, associated with the provision of climate information. Relative to the control sample, farmers with access to enhanced climate information reduced their cropped area, invested in more intensive crop management, and achieved higher yields with attractive returns on investment relative to farmers in control villages. Farmers from treatment villages also demonstrated appreciation of the role of climate information in planning and managing farm activities, higher satisfaction with the season, and strong interest in receiving climate information on a regular basis. This interest was demonstrated by their willingness to pay a modest amount for the service if required. The evaluation was disaggregated by gender. Gender influenced adjustments to crop mix in response to climate information, with women preferring short-duration legumes. Gender did not appear to affect the subjective value put on climate information, or willingness to pay. The study findings suggest that both of the workshop-based approaches to communicating climate information improved farers’ ability to manage risks. However the sample size was not sufficient to provide conclusive evidence of the impact on yields, investments or livelihoods. It is therefore suggested that similar assessments with a much larger sample in different agro-ecologies, and more comprehensive baseline data collection, be planned to make a more conclusive assessment of farmers’ ability to understand, utilize and benefit from seasonal climate forecast information. Such a study should aim to develop and refine training 3 modules that can help farmers and their support agents better understand climate variability, probabilistic forecasts and their application, and appropriate communication systems aimed at providing timely access to required climate information.